Detention without trial: historical evolution, states' authority and international law - Zamani, Masoud (2015)
In the wake of the US detention policy in the aftermath of the 9/11 attacks, the practice of detention without trial has gained a degree of attention unparalleled in the history of common law tradition. Legal analyses of all kinds have ensued, and countless policy plans and guidelines have been created. Yet, despite the pedigree of detention without trial, the historical dimension to the practice of detention without trial has not been invested with the scrutiny that it deserves. Drawing on the history of detention without trial in Britain, this research seeks to draw a roadmap for the evolving features of detention without trial. It will be argued that it is by virtue of this historical understanding that we can make sense of the modern laws governing the practice of detention without trial and its associated features.